Functional free-standing graphene honeycomb films - Sun, Hang (2014)
Fabricating free-standing, three-dimensional (3D) ordered porous graphene structure can service a wide range of functional materials such as environmentally friendly materials for antibacterial medical applications and efficient solar harvesting devices. A scalable solution processable strategy is developed to create such free-standing hierarchical porous structures composed of functionalized graphene sheets via an “on water spreading” method. The free-standing film shows a large area uniform honeycomb structure and can be transferred onto any substrate of interest. The graphene-based free-standing honeycomb films exhibit superior broad spectrum antibacterial activity as confirmed using green fluorescent protein labeled Pseudomonas aeruginosa PAO1 and Escherichia coli as model pathogens. Functional nanoparticles such as titanium dioxide (TiO2) nanoparticles can be easily introduced into conductive graphene-based scaffolds by premixing. The formed composite honeycomb film electrode shows a fast, stable, and completely reversible photocurrent response accompanying each switch-on and switch-off event. The graphene-based honeycomb scaffold enhances the light-harvesting efficiency and improves the photoelectric conversion behavior; the photocurrent of the composite film is about two times as high as that of the pure TiO2 film electrode. Such composite porous films combining remarkably good electrochemical performance of graphene, a large electrode/electrolyte contact area, and excellent stability during the photo-conversion process hold promise for further applications in water treatment and solar energy conversion.